T4 Phage Tail Adhesin Gp12 Counteracts LPS-Induced Inflammation In Vivo - Miernikiewicz, Paulina; Kłopot, Anna; Soluch, Ryszard; Szkuta, Piotr; Kęska, Weronika; Hodyra-Stefaniak, Katarzyna; Konopka, Agnieszka; Nowak, Marcin; Lecion, Dorota; Kaźmierczak, Zuzanna; Majewska, Joanna; Harhala, Marek; et al. (Frontiers in Microbiology, 2016)
Bacteriophages that infect Gram-negative bacteria often bind to the bacterial surface by interaction of specific proteins with lipopolysaccharide (LPS). Short tail fiber proteins (tail adhesin, gp12) mediate adsorption of T4-like bacteriophages to Escherichia coli, binding surface proteins or LPS. Produced as a recombined protein, gp12 retains its ability to bind LPS. Since LPS is able to exert a major impact on the immune response in animals and in humans, we have tested LPS-binding phage protein gp12 as a potential modulator of the LPS-induced immune response. We have produced tail adhesin gp12 in a bacterial expression system and confirmed its ability to form trimers and to bind lipopolysaccharide in vitro by dynamic light scattering. This product had no negative effect on mammalian cell proliferation in vitro. Further, no harmful effects of this protein were observed in mice. Thus, gp12 was used in combination with LPS in a murine model, and it decreased the inflammatory response to LPS in vivo, as assessed by serum levels of cytokines IL-1 alpha and IL-6 and by histopathological analysis of spleen, liver, kidney and lungs. Thus, in future studies gp12 may be considered as a potential tool for modulation and specifically for counteracting LPS-related physiological effects in vivo.